2003
DOI: 10.1111/j.1750-3639.2003.tb00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Adhesion of Primary Human Schwannoma Cells is Dependent on Altered Expression of Integrins

Abstract: Mutations in the tumor suppressor gene coding for merlin cause Neurofibromatosis type 2 (NF2), all spontaneous schwannomas, and a majority of meningiomas. Merlin links transmembrane proteins to the cytoskeleton. Accordingly, primary human schwannoma cells lacking merlin show an increased number of lamellipodia and filopodia as well as increased cell spreading. We show enhanced adhesion in primary human schwannoma cells and present evidence that this is dependent on the integrin chains α6β1 and α6β4. We further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 49 publications
2
37
0
Order By: Relevance
“…Loss of merlin in schwannomas leads to pathological adhesion [11,12]. Utermark et al [12] showed that the enhanced adhesion is linked to increased expression of integrins a6, b1 and b4 at protein level and mRNA level.…”
Section: Integrins and Related The Rac/pak/jnk Fak/src And Mtorc1 Pamentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of merlin in schwannomas leads to pathological adhesion [11,12]. Utermark et al [12] showed that the enhanced adhesion is linked to increased expression of integrins a6, b1 and b4 at protein level and mRNA level.…”
Section: Integrins and Related The Rac/pak/jnk Fak/src And Mtorc1 Pamentioning
confidence: 99%
“…Loss of merlin in schwannomas leads to pathological adhesion [11,12]. Utermark et al [12] showed that the enhanced adhesion is linked to increased expression of integrins a6, b1 and b4 at protein level and mRNA level. The upregulation of integrins a6, b1 and b4 was confirmed in an array analysis when mRNA from schwannomas was compared to Schwann cells [13].…”
Section: Integrins and Related The Rac/pak/jnk Fak/src And Mtorc1 Pamentioning
confidence: 99%
“…Integrins are transmembrane receptors that mediate cell-matrix or cell-cell adhesion, and transduce signals that regulate gene expression and cell growth, including Schwann cells. Altered expression of the ITGB4 has been shown in schwannomas (37) and MPNSTs (5). Therefore, it is likely that the amplification of ITGB4 gene provides growth advantage to the Schwann cells in malignant tumors.…”
Section: Deleted Genesmentioning
confidence: 99%
“…Using our in vitro model for human schwannoma, we have previously shown that merlin loss leads to enhanced proliferation and decreased apoptosis (5), increased cell-matrix adhesion (due to the overexpression of integrins; ref. 6), and decreased cell-cell adhesion (7). The RhoGTPases Rac1 and Cdc42 and their downstream effector p21-activated kinase (PAK) are activated in human primary schwannoma cells and have been linked to the aforementioned characteristics of schwannoma cells (8,9).…”
Section: Introductionmentioning
confidence: 99%